THE ANALYSIS OF INVESTMENT CAPACITY OF SOCIAL PROJECTS IMPLEMENTATION IN UNITED TERRITORIAL COMMUNITIES (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Intruduction. Decentralization in Ukraine has caused considerable discussion regarding its correctness and efficiency. On the one side, new successful united territorial communities have emerged, that have budgets of small towns and are developing rapidly. On the other way, there are a huge number of insolvent communities, that haven’t money for minimum needs concerning support for social infrastructure and payment of wages.The purpose of the article. The purpose of the article is research theoretical and applied principles of condition prospects for socio-economic development of united territorial communities in Ukraine. According to the set goal, the following research tasks have defined: to reveal the essence and components of the concept of «decentralization»; to explore the features of  functioning in united territorial communities in Volyn region; to analyze social investment projects that have implemented by united territorial communities.Results. Combining and generalizing all interpretations and approaches we can confirm that there isn’t the single common definition of “decentralization” and opinion’s unity regarding its composition, structure and methods of manifestation. Based on conducted research, we have formed our own vision of the essence of this category we mean decentralization as a system of interrelated economic and legal measures that have aimed for improving the socio-economical condition of local government by applying the principles of synergy and inclusiveness which provides improving the level and quality of life of the population maximum involvement of community members to development of social product and to ensure a fair distribution of goods received.The implemented changes of Budget and Tax Codes of Ukraine have caused to significant increase in the share of local budget revenues from UAH 68.6 billion in 2014 to UAH 267 billion in 2019. Such redistribution of financial flows has caused to rapid development of united territorial communities increased the efficiency of funds for development of local infrastructure and improving the social and living conditions of citizens.54 united territorial communities have been formed in Volyn region and two communities occupy leading positions in Ukraine on growth of incomes of the general fund of local budgets on one inhabitant. However, there is a problem in the region of significant disparity in local budget revenues that caused by the specifics of payment PDFO by large enterprises at the place of their registration. Such situation has developed in Boratyn’s and Pidhaitsi’s united territorial communities. There are large enterprises (Ltd. “Kromberg and Shubert Lu” and Ltd. “Modern Expo”, respectively), and its workers have been registered and are living in Lutsk or other settlements of the region.Conclusions. Administrative and territorial reform must take place within the framework of the state strategy of regional development should consider the following priority areas: streamlining the legal and regulatory framework; ensuring consistency of practical processes, implementation of decentralization reform with its strategic goals; introduction of the involvement procedure representatives of local self-government to the examination of bills; introduction of the procedure of involving representatives of local self-government in the examination of draft laws; restructuring of the Regional Development Council President of Ukraine with the provision of strategic interdepartmental coordination functions; determining the future model of district division and appropriate management structure for minimization of the level of conflict along the line "district - community"; strengthening the fiscal capacity and financial independence of communities changes in the taxation system (crediting the tax on individuals to local budgets at the place of person's residence but not the place of employment); stimulation of Ukrainian and foreign business to invest in local UTC projects on a parity basis; establishing the procedure for granting loans to local budgets from commercial banks to finance investment projects of local significance, and also introduction  the institute of municipal bank.The prospects for further research we have been perceiving in developing effective mechanisms for co-financing investment projects social orientation from the state and local budgets, grants, private investors, etc
Keywords: investing, social project, united territorial community